2020
DOI: 10.1007/s10096-020-03811-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Shigella flexneri isolated from pediatrics in a diarrhea-endemic area of Khyber Pakhtunkhwa, Pakistan

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[7][8][9][10][11][12][13]20,21 Several studies reported evidence about association of S. flexneri serotype with antibiotic resistance pattern. [4][5][6][7][8][9][10][11][12][13][14] The current study is highlighting the molecular serotyping of S. flexneri and their association with antimicrobial resistance patterns in Pakistan. The serotype 2b was observed as most frequent serotype followed by serotype 1b which is in line with previous studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13]20,21 Several studies reported evidence about association of S. flexneri serotype with antibiotic resistance pattern. [4][5][6][7][8][9][10][11][12][13][14] The current study is highlighting the molecular serotyping of S. flexneri and their association with antimicrobial resistance patterns in Pakistan. The serotype 2b was observed as most frequent serotype followed by serotype 1b which is in line with previous studies.…”
Section: Discussionmentioning
confidence: 88%
“…A total of 199 S. flexneri isolates isolated from stool samples of pediatric diarrheal patients up to age of 17 years at tertiary care hospitals of Khyber Pakhtunkhwa, Pakistan, (Nisa et al, 2020) 14 and nonclinical samples (drinking water and raw milk, fruits/vegetables from markets [unpublished work] of Pakistan) from January 2016 to May 2017 were included in the analysis.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…The present study includes 199 S. flexneri strains including 155 clinical strains isolated from stool samples collected from different diarrheal patients with mean age of 9.12 before any prescribed antibiotic treatment visiting at various tertiary care hospitals of Peshawar and 44 non-clinical strains isolated from different various non-clinical sources (household drinking water, retail raw milk, and fruits/ vegetables) from different towns of Peshawar. All these S. flexneri strains were previously characterized by 16S rRNA sequencing and molecular serotyping [18][19][20]. Both clinical and non-clinical samples were further processed for analysis of antibiotic susceptibility testing.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…A total of 199 identified S. flexneri strains including 155 clinical strains from diarrheal patient's stool (Nisa et al, 2020) and 44 nonclinical strains (drinking water: 22, and retail rawfood: 22) collected from January 2016 to May 2017 in Pakistan (unpublished work). Molecular serotyping were performed for S. flexneri isolates using a multiplex PCR assay (Sun et al, 2011).…”
Section: Bacterial Strainsmentioning
confidence: 99%